Computerized analysis of multiple-mammographic views potential usefulness of special view mammograms in computer-aided diagnosis. - Zhimin Huo (IEEE Transactions on medical imaging)
Purpose: To investigate the potential usefulness of special view mammograms in the computer-aided diagnosis of mammographic breast lesions. Materials and Methods: Previously, we developed a computerized method for the classification of mammographic mass lesions on standard-view mammograms, i.e., mediolateral oblique (MLO) view and/or cranial caudal (CC) views. In this study, we evaluate the performance of our computerized classification method on an independent database consisting of 70 cases (33 malignant and 37 benign cases), each having CC, MLO, and special view mammograms (spot compression or spot compression magnification views). The mass lesion identified in each of the three mammographic views was analyzed using our previously developed and trained computerized classification method. Performance in the task of distinguishing between malignant and benign lesions was evaluated using receiver operating characteristic analysis. On this independent database, we compared the performance of individual computer-extracted mammographic features, as well as the computer-estimated likelihood of malignancy, for the standard and special views. Results: Computerized analysis of special view mammograms alone in the task of distinguishing between malignant and benign lesions yielded an A z of 0.95, which is significantly higher (p < 0.005) than that obtained from the MLO and CC views (A z values of 0.78 and 0.75, respectively). Use of only the special views correctly classified 19 of 33 benign cases (a specificity of 58%) at 100% sensitivity, whereas use of the CC and MLO views alone correctly classified 4 and 8 of 33 benign cases (specificities of 12% and 24%, respectively). In addition, we found that the average computer output of the three views (A z of 0.95) yielded a significantly better performance than did the maximum computer output from the mammographic views. Conclusions: Computerized analysis of special view mammograms provides an improved prediction- - of the benign versus malignant status of mammographic mass lesions.